Learning Management System vs Conventional Assessment: Reviewing the Best Assessment for English subjects - Priyeti, Shintia; Degeng, Made Duananda Kartika; Wedi, Agus (Journal La Sociale, 2025)
Technological advances in education have encouraged innovation in learning assessment methods, including in English subjects. This article discusses the effectiveness of Learning Management System (LMS) versus conventional assessment in measuring students' English proficiency. Based on a systematic literature review of 15 journals, it explores the advantages and disadvantages of each method, such as speed of feedback, student engagement, and measurement accuracy. Results show that LMS-based assessments offer efficiency, interactivity and the ability to provide detailed data on student performance. However, challenges such as limited access to technology and lack of direct interaction are obstacles. In contrast, conventional assessments outperform in the aspects of social interaction and direct observation, although they are often slower and prone to subjective bias. This study concludes that the LMS has greater potential in improving English learning outcomes, but a combination of both approaches can be an optimal solution. The implications of this study provide insights for educators and policy makers in designing a more effective technology-based curriculum.